Utilize BIM Technology for Achiveing Sustainable Passengers Terminal in Baghdad International Airport - Fatima M. Kareem; Abbas M. Abd; Requiem N. Zehawi (Diyala Journal of Engineering Sciences, 2021)
The construction of airport infrastructures usually consumes huge amount of energy. In fact, the airport buildings are among the largest energy consumers entities due to their huge size and special operation pattern as well as their unique configuration that facilitate the large number of accommodated passengers. Despite the local energy shortage in Iraq in the last two decades, there is a quite scarce number of researches that deal with sustainable airport buildings. The aim of this research is to analyze the terminal building in Baghdad International Airport in order to find out the best set of modifications that result in an optimal energy consumption and least carbon dioxide emissions. The analysis was conducted by the use of Building Information Modelling (BIM) technology and the associated programs such as; Auto desk Revit 2021 and Auto desk Insight 360, in order to determine the optimal strategies by which the most applicable alternative construction materials and procedures are considered in order to obtain an environmentally and economically sustainable airport terminal buildings. By applying this analysis on Nineveh terminal building in Baghdad International Airport revealed that many alternatives are capable of making tangible reduction in the Energy Use Intensity (EUI). Such reductions are noticed when altering, in the optimum manner, the windows configurations in terms of size, glazing type, and shadings. The alteration of construction materials for walls and roofs also reduces the EUI. It was also found out that the change in lighting control systems and lighting efficiency may reduce EUI. But the major impact could be resulted when altering the Heating/Ventilating/ Air conditioning Systems (HVAC) in the optimum manner which reduces the EUI by 67.15kw/m2/year, and the proper use of photovoltaic panels which provides a sustainable electricity and reduces EUI by 57.08 kWh/m2/year.  Accordingly; in the quest of the best procedure to develop a sustainable terminal building, it is highly recommended to alter the HVAC systems and the utilization of the photovoltaic panels on rooftops.